ИИВ ОЛИЙ ТАЪЛИМ ТИЗИМИ КУРСАНТЛАРИДА ЎҚУВ МОТИВАЦИЯ: МУАММО ВА ЕЧИМЛАР - Тургунов, Н.Ш. (SCIENCE and SOCIETY, 2024)
This article the cadets of the higher education system of the Ministry of Internal Affairs expressed their opinions on the problems and solutions of educational motivation, the social psychological factors of its improvement.
Keywords: educational motivation; learning; activity; external and internal motives; motivating action; educational process; social; professional success